Roll‐to‐Roll Reverse‐Offset Printing Combined with Photonic Sintering Process for Highly Conductive Ultrafine Patterns. Issue 10 (18th June 2020) - Zhong, Zhaoyang; Ko, Pyeongsam; Seok, Jae Young; Kim, Hyuntae; Kwon, Sin; Youn, Hongseok; Woo, Kyoohee
Abstract : Herein, a roll‐to‐roll (R2R) continuous reverse‐offset (RO) printing process combined with an intense pulsed light (IPL) sintering technique for the mass production of Ag nanoparticles (NPs)‐based highly conductive, ultrafine patterns on the low‐cost, heat‐sensitive polyethylene terephthalate (PET) substrate is first explored. Variations in printing quality depending on the ink‐coating thickness and the applied pressure during the off process and printing times are observed. By these observations, their effects on pattern quality are identified, and the blanket swelling responsible for printing stability degradation is solved using infrared (IR) exposure. By analyzing the thermal behavior of RO ink, the microstructures of patterns as IPL irradiation conditions are investigated. Contrary to the case of high‐power light for a short time, a steady and gradual volume change is induced in the pattern irradiated by low‐power light for a long time so that cracks and pores are considerably suppressed. The R2R inline production of densely sintered mesh (less than ≈10 μm) transparent electrodes ( R s = 9.86 ± 0.36 Ω sq −1 at T ≈ 90%) is successfully demonstrated via successive IPL irradiations synchronized with printing velocity. Finally, the potential use of R2R‐produced electrodes is clearly proved by fabricating flexible organic light‐emitting diodes (OLEDs). Abstract : Roll‐to‐roll (R2R)‐based reverse‐offset printing combined with the photonic sintering process is explored for the inline production of Ag nanoparticles‐based ultrafine highly conductive patterns. Printability depending on printing process parameters and sintering behavior as light‐irradiation conditions is examined. Finally, the inline produced fine mesh transparent electrodes are successfully implemented in a flexible organic light‐emitting diode.